Semaphorin 7A is protective during inflammatory peritonitis through integrin receptor signaling - Körner, Andreas; Köhler, David; Schneider, Mariella; Roth, Judith M.; Granja, Tiago F.; Eggstein, Claudia; Mirakaj, Valbona; Rosenberger, Peter (Frontiers in Immunology, 2023)
Introduction The study explores the role of endothelial Semaphorin 7A (SEMA7A) in inflammatory processes. SEMA7A is known for enhancing inflammation during tissue hypoxia and exhibiting anti-inflammatory properties in the intestinal system during colitis. This research extends the understanding of SEMA7A's function by examining its role in inflammatory peritonitis and intestinal inflammation. Methods The research involved inducing peritonitis in SEMA7A knockout (SEMA7A-/-) and wild-type (WT) animals through Zymosan A (ZyA) injection. The inflammatory response was assessed by measuring cell count and cytokine release. In parallel, the study investigated the expression of SEMA7A in intestinal epithelial cells under inflammatory stimuli and its impact on interleukin 10 (IL-10) production using an in vitro co-culture model of monocytes and epithelial cells. Additionally, the distribution of SEMA7A target receptors, particularly ITGAV/ITGB1 (CD51/CD29), was analyzed in WT animals. Results The results revealed that SEMA7A-/- animals exhibited increased inflammatory peritonitis compared to the WT animals. Inflammatory conditions in intestinal epithelial cells led to the induction of SEMA7A. The co-culture experiments demonstrated that SEMA7A induced IL-10 production, which depended on integrin receptors and was independent of PLXNC1 expression. Furthermore, ITGAV/ITGB1 emerged as the predominant SEMA7A receptor in the intestinal area of WT animals. Discussion These findings underscore the multifaceted role of SEMA7A in inflammatory processes. The differential responses in peritonitis and intestinal inflammation suggest that SEMA7A's function is significantly influenced by the expression and distribution of its target receptors within different organ systems. The study highlights the complex and context-dependent nature of SEMA7A in mediating inflammatory responses.